PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MEDIA INTERAKTIF GENIALLY TERHADAP KETERAMPILAN MENULIS TEKS HIKAYAT - Hanna Zalfa Mulyawati; Ratna Dewi Kartikasari (Jurnal Bastra (Bahasa dan Sastra), 2025)
This study was motivated by the low level of students' skills in writing hikayat texts and their lack of interest in writing. To address this issue, the researcher implemented the Discovery Learning model assisted by Genially interactive media in hikayat text writing instruction. The aim of this study was to determine the effect of the Discovery Learning model supported by Genially media on students' hikayat writing skills. The research was conducted at SMK Al Amanah with 63 tenth-grade students, consisting of 30 students in the experimental group (X OTKP 2) and 33 students in the control group (X OTKP 1). The sampling technique used was simple random sampling. This study employed a quantitative approach with a true experimental method and a post-test-only control group design. The instrument used was a hikayat writing test, assessed based on several aspects: structure, plot, language use, moral message, and creativity. The t-test results showed a t-value of 8.727 with degrees of freedom (df) = 61 and a significance value (2-tailed) of 0.000 < 0.05. Based on these results, the null hypothesis (H0) was rejected, and the alternative hypothesis (H1) was accepted. Thus, the study concludes that the Discovery Learning model assisted by Genially interactive media has a significant effect on improving students' hikayat text writing skills.